Negotiating Humanitarian Narratives: Visual Framing of the Rohingya Crisis on Reuters and Anadolu Ajansı’s Instagram - Durrotul Mas'udah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Visual journalism plays a pivotal role in shaping public understandings of humanitarian crises by constructing particular representations of suffering, responsibility, and displacement. Despite Instagram's growing importance as a platform for visual news, its role in framing humanitarian issues remains underexplored. This study employs qualitative content analysis to examine the visual framing of the Rohingya crisis on the Instagram accounts of two different international news agencies namely and Anadolu Ajansı. The analysis focuses on photographs, captions, and hashtags, examining visual codes including the category of people, camera distance, facial expressions, and demographic representation. The findings show that both news organizations predominantly frame the Rohingya crisis through a humanitarian lens, emphasizing refugees' vulnerability and experiences of forced displacement. However, they adopt different framing strategies. Anadolu Ajansı combines personalized portrayals of individual suffering with images of mass displacement and provides explicit contextualization through captions and hashtags that identify the causes of the crisis and emphasize the victims' religious identity as Rohingya Muslims. In contrast, Reuters adopts a more documentary and event-oriented approach, focusing primarily on refugees' experiences during and after displacement while providing less contextual explanation. These findings demonstrate that visual framing on Instagram is constructed through the interplay of photographs, captions, and hashtags, highlighting how different journalistic strategies shape public understandings of humanitarian crises in digital media environments.